Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1108/01425450710720011
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the potential of high performance work systems in SMEs

Abstract: Purpose -Aims to explore aspects of employee relations in firms included within The Sunday Times list of the UK's "Best Small Companies to Work For", focusing in particular on the use of high performance work systems (HPWS), and the way they impact upon performance in these businesses. Design/methodology/approach -The research is based upon a postal survey supplemented by detailed face-to-face interviews with CEOs in 60 per cent of the ranked firms. Findings -The SMEs studied are found to be highly successful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(91 citation statements)
references
References 29 publications
2
82
0
7
Order By: Relevance
“…The decision to delegate and empower employees will be made more quickly by entrepreneurs who have a better understanding of the added value of best practices. Supportive findings for this reasoning were reported by Drummond and Stone (2007) who found that in a population of best small firm employers, owner-managers stated that they had a strong belief in the advantages of involving employees in teamwork, in developing the firm strategy, in daily managerial routines and in designing their own work. These arguments lead to our third pair of hypotheses:…”
Section: Best-practice Awarenessmentioning
confidence: 62%
See 4 more Smart Citations
“…The decision to delegate and empower employees will be made more quickly by entrepreneurs who have a better understanding of the added value of best practices. Supportive findings for this reasoning were reported by Drummond and Stone (2007) who found that in a population of best small firm employers, owner-managers stated that they had a strong belief in the advantages of involving employees in teamwork, in developing the firm strategy, in daily managerial routines and in designing their own work. These arguments lead to our third pair of hypotheses:…”
Section: Best-practice Awarenessmentioning
confidence: 62%
“…Therefore, whether HPWPs are adopted depends on the beliefs of the entrepreneur with respect to the benefits of HRMrelated interventions as a solution for business issues (Cassell et al 2002). This is illustrated by the finding that small firm owners consistently report that HR practices need to 'fit' their firm's conditions and needs (Drummond and Stone 2007;Harney and Dundon 2006). To further investigate this aspect, this paper builds on the decision-making models proposed by Cassell et al (2002) and de Kok and Uhlaner (2001) which hold that the decision by a small firm's management to translate a company issue into an HR intervention depends on both the owner-manager's ability to make sense of the issue at stake and his/her strategic choice to apply the available resources (time and money).…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations